Nakadake sanroku kamaatogun no kenkyū = Studies on the Nakadake Sanroku Kiln Site Cluster - Nakamura, Naoko; Shinoto, Maria (Kagoshima Daigaku Maizō Bunkazai Chōsa Sentā, 2015)
Studies on the Nakadake Sanroku Kiln site cluster